(3QSGdI aj Gdadcs
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdMeO ddg Bjg GdMeO hGLHI HGdcJGH hGdSfI dCf YOO CjGe GdSfI GdTeSjI KdGKeGFI hNeSI hSJhf jhekG s
(3BNQgG (B:s
(3hGdLfhH LfhHkG dCfgG JgH ef GdLGfH GdCjef GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(3 d) s
Keywords: (3GdeLGejYs